Managing Difficult Fractures due to Ballistic Trauma with Ilizarov Ring Fixation - Chand, Pankaj; Shrestha, Roshan Lal; KC, Bachu Ram; Shah, Bhanu Chand; Joshi, Amit; Thapa, Bishnu Nahadur (Medical Journal of Shree Birendra Hospital, 2010)
20 fractures (7 femoral and 13 tibial) were treated with the illizarov apparatus between 2003 to 2006. Allwere old injuries, previously managed by internal fixation (intramedullary rods), external fixation (Hoffman'sexternal fixators), or conservatively with traction and plaster of paris slabs. Ilizarov fixators were appliedto manage infected non-union with or without bone loss and malunion. Corticotomy and bone transportwas carried out in cases with significant bone loss. In others without any limb shortening and minimalbony defect, bone grafting and compression was carried out. In one case valgus deformity along withnon-union was corrected. Early weight bearing with range of motion exercises for ankle and knee jointswere encouraged. Average fracture healing time was 12 months (8 to 18 months). All fractures healed with